High pathogenicity of emerging porcine G9P[23] and G11P[7] rotavirus for newborn piglets in China - Zhang, Zhendong; Li, Duo; He, Sun; Du, Jiubin; Li, Yubo; Liu, Qiangde; Wang, Pengjiang; Wang, Wenqiang; Wen, Wei; Zhu, Zhenbang; Tang, Xudong; Li, Xiangdong (Frontiers in Veterinary Science, 2025)
In order to better understand the pathogenicity of the current porcine A group rotavirus (PoRVA) field strains, AHBZ2304 (G9P[23]) and AHBZ2303 (G11P[7]) isolated from diarrhea suckling piglets were selected for pathogenicity analysis in the present study. Experimental inoculation of colostrum-deprived 2-day-old piglets revealed that both isolates caused severe clinical sings, high level of virus shedding and significant damage to the small intestinal villi. Additionally, both gross and microscopic lung lesions were identified at 72 h post infection (HPI) compared to control. Alterations in the microbiota and the overexpression of inflammatory cytokines may serve as critical mechanisms driving the bowel disease associated with PoRVA infection. Our results are of great significance for understanding the pathogenicity of PoRVA emerged in recent years, highlighting the potential for porcine rotavirus to become epidemic and complex, and necessitating heightened attention of the often-overlooked disease in the field.